1984
DOI: 10.1017/s0022172400060927
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of the original Rappaport medium (R medium) and the Rappaport–Vassiliadis medium (RV medium) in the isolation of salmonellae from meat products

Abstract: SUMMARYThe Rappaport-Vassiliadis enrichment medium (RV medium) in 10 ml quantities (RV/43°C, 10 ml) inoculated with 0-1 ml of pre-enrichment medium (P medium) was found more efficient in the isolation of salmonellae from 409 pre-enriched samples (mainly meat products), than the original Rappaport medium incubated at 43°C (R/43°C) and the RV medium in 5 ml quantities (RV/43°C, 5 ml) inoculated with 0-01 ml of P medium (P < 0-001, in both instances). Therefore, the inoculum from pre-enriched foods should not be … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

1984
1984
2010
2010

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…In studying the effect of inoculation ratio on the efficiency of salmonella isolation from polluted water Harvey & Price (1983) suggested that a ratio of 1:20 was superior for RV medium. In complete contrast, we have shown that a ratio of 1:lOO gives significantly better results ( P < 0.001) for both seagull faecal material and polluted water and this is supported by the findings of other workers (van Schothorst & Renaud 1983;Vassiliadis et al 1984;Fricker 1984b). The reasons for the discrepancy in the results obtained by different groups is unclear and requires further investigation.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In studying the effect of inoculation ratio on the efficiency of salmonella isolation from polluted water Harvey & Price (1983) suggested that a ratio of 1:20 was superior for RV medium. In complete contrast, we have shown that a ratio of 1:lOO gives significantly better results ( P < 0.001) for both seagull faecal material and polluted water and this is supported by the findings of other workers (van Schothorst & Renaud 1983;Vassiliadis et al 1984;Fricker 1984b). The reasons for the discrepancy in the results obtained by different groups is unclear and requires further investigation.…”
Section: Discussionsupporting
confidence: 88%
“…Many studies (Vassiliadis et al 1978(Vassiliadis et al , 1984Fricker et al 1983;Fricker 1984b) have report-* Present address: Department of Microbiology, University of Reading, London Road, Reading RG1 5AQ, UK. ed that the RV medium is as efficient or is more efficient than R25 medium (Vassiliadis et al 1970), although Harvey & Price (1983) suggested that R25 was the better of the two media when used for the isolation of salmonellas from polluted water.…”
mentioning
confidence: 99%
“…Micrococci/staphylococci were counted on Baird‐Parker Agar (Oxoid) at 37C for 24–48 h (Pichhardt 1993). The numbers of S. Typhimurium were estimated by using the most probable number (MPN) method described by Vassilliadis et al . (1984).…”
Section: Methodsmentioning
confidence: 99%
“…It was found that an inoculum of 0.1 ml of pre-enrichment culture of meat products in buffered peptone water, introduced to 10 ml of Rappaport-Vassiliadis medium (RV medium) incubated at 43°C (inoculum ratio 1: 100) was significantly more efficient in the isolation of salmonellas than an inoculum of the size of 0-02 ml (inoculum ratio 1:500) (Vassiliadis et al 1978(Vassiliadis et al , 1984. It was also observed that inocula of pre-enrichment cultures of minced meat, of the size of 0 5 ml and 1P0 ml to 10 ml of RV medium (inoculum ratios 1:20 and 1: 10) were significantly less efficient than an inoculum of 0-1 ml (Vassiliadis et al, unpublished data, 1978).…”
Section: Introductionmentioning
confidence: 99%